Ngaji Fiqh Zakat: Empowerment of Amil Zakat at Simbarwaringin Village - Ismail, Habib; Rahmawati, Rita; Farida, Annikmah; M. Muslih; Irhamuddin; Karini, Eti (Ihsanniat: Jurnal Pengabdian Kepada Masyarakat, 2025)
This service aims to improve the understanding of the community, especially Amil Zakat, about the importance of effective Zakat management in order to empower the community in Simbarwaringin Village. The Ngaji Fiqh Zakat program organized by the Nahdlatul Ulama (NU) Branch is presented as a forum for education about Fiqh Zakat, with speakers KH. Andi Ali Akbar, Deputy Secretary of Syuriah Nahdlatul Ulama Regional Management Lampung. Through this mentoring session, Amil Zakat and the community are given an understanding of the obligation of Zakat, types of Zakat, and the principles of targeted Zakat distribution. The method used is participatory mentoring that directly involves Amil Zakat and the community in every stage of the activity. A better understanding of Zakat can increase the awareness and skills of Amil Zakat in managing Zakat in a transparent and accountable manner, which contributes to improving the welfare of local communities.